Approach to the Contemporary Public Sphere: fittings out from the cultural production and psychopathic traits (Encuentros, 2016)
This paper is an approach to a "new configuration" of the public sphere. With this purpose, we consider the present articulations between forms of cultural production and some renewed intervention in the public space, in relation the uses and the Internet possibilities, and the communication technologies. In this way, we understand that the public space is enlarged, so must be rethought the metaphors and territorial terms to understand it, with the incorporation and expansion of "virtual-technological" in the everyday life. The article is part of a essay and analytical style with an interpretative methodology: materials used as contemporary reflections and some current practices and cultural products. In its conclusions, pointing a set of coordinates to interpret contemporary processes in relation to the expansion of the virtual public space, new forms of collective action for the appropriation of devices and virtual tools and new features of the intellectual field given by enabling new areas of "public statement".Keywords: public sphere, technologies, Internet, public space